Energy Yields and Wind Loads of Alternative PV Designs for Roofs in Snowy Climates ... - Svedjeholm, Maria; Lampa, Josefin; Petersson, Anna Malou; Olofsson, Arvid; Andersson, Robin; Fooladgar, Ehsan; Estola, Pirjo; Lindh, Mattias (WIP-Munich, 2024)
If large-scale rooftop photovoltaic is to reach its full potential in snow rich climates, energy production losses caused by snow shading need to be alleviated. Here we investigate the energy performance and wind loads of five alternative PV system designs, conceived to reduce the snow shading losses in these environments. For the town of Luleå (Sweden, 65°N) we find that all alternative designs perform better than the conventional reference in terms of snow shading losses and annual specific energy yield, but that elevated high-tilt designs are exposed to high wind loads and lower energy production per roof area. In our view, a variant of a conventional system that is elevated above the expected snow depth make out a promising design for strong roofs, since it features very low wind loads, small snow shading losses, and high energy production per roof area. For weaker buildings that require snow removal, we instead suggest less surface efficient, elevated high-tilt designs with large enough row spacing for ...